1987
DOI: 10.1002/tcm.1770070205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylene glycol monomethyl ether on spermatogenesis, dominant lethality, and F1 abnormalities in the rat and the mouse after treatment of F0 males

Abstract: Adult male CD rats and CD-1 mice were given a single oral dose of ethylene glycol monomethyl ether (EGM) at 0, 500, 750, 1,000, or 1500 mg/kg. Groups of 10 were killed at weekly intervals after dosing for analysis of sperm counts and morphology or testicular histology; further groups of 10 were sequentially mated to pairs of virgin females to test for dominant lethality or gross foetal malformations in the F1 generation (F1 abnormalities). EGM was found to deplete the spermatocytes of both species severely, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
(2 reference statements)
0
13
0
2
Order By: Relevance
“…5). However, if the dose level is raised further (750 mg/kg/day), spermatids and spermatogonia are also affected (2).…”
Section: Spermatogenesismentioning
confidence: 99%
“…5). However, if the dose level is raised further (750 mg/kg/day), spermatids and spermatogonia are also affected (2).…”
Section: Spermatogenesismentioning
confidence: 99%
“…There are several compounds that have already been identified as cellular targets for the induction of sperm morphological abnormalities, such as ethylene glycol monomethyl ether (EGME) for spermatocytes (Anderson et al, 1987); boric acid for mid spermatid (Linder et al, 1990); dibromo acetic acid (DBAA) for late and/or elongating spermatid (Linder et al, 1994). Although the terminology employed in each study was different, substantially the same finding of "tailless sperm" has been consistently observed as a major finding among the studies, such as EGME, separated heads (Anderson et al, 1987); boric acid, decapitation and no head (Linder et al, 1990;Yoshizaki et al, 1999); DBAA, isolated heads (Tsuchiya et al, 2000). Since the tailless sperm have been detected in the sperm morphological examination regardless of the cellular target, it can be suggested that the tailless sperm counting is a robust measure in the sperm morphological examination for the detection of spermatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Die hohen Dosierungen wirkten zytotoxisch im Knochenmark (Au et al 1996). Aus drei publizierten Dominant-Letal-Tests (Anderson et al 1987;McGregor et al 1983;Rao et al 1983) an Nagern ergeben sich keine eindeutigen Hinweise auf die Induktion von dominanten Letalmutationen, da die beobachteten Präimplantationsver-luste vermutlich auf die spermatotoxische Wirkung des 2-Methoxyethanol zurückzu-führen sind (BUA 1997). Ein erhöhter Postimplantationsverlust wurde bei CD-Ratten nach einmaliger oraler Gabe von 500, 750, 1000 bzw.…”
Section: -Methoxyethanolunclassified